Selling Price and Time on the Real Estate Market : A Meta-Analysis - Kuncová, Barbora; Čadil, Jan; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The aim of the thesis is to broaden the research in the field of housing economics using the statistical tool of meta-analysis. The thesis examines the relationship between the selling price of a house and the time the house spends at the housing market. Although the research investigating this relation is of a wide comprehension, the results arising from various primary studies differ a lot. The goal of the thesis is to explain the source of this heterogeneity and determine the factors causing this variation. According to the results, it can be concluded that the effect size is influenced mainly by number of observations, modelling technique and specification of the model. Median income or location are other factors also determining the size of estimated coefficients. Also publication bias has been investigated although its presence is not confirmed in this thesis.
Vedoucí práce: Jan Čadil
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses